MOBILE DICTIONARY - Ibrahim, Siti Nabilah (Universiti Teknologi Petronas, 2005)
Having difficulties in understanding the meaning of particular word in a particular language is unavoidable. The solutionfor this concern is either paper-based or electronic dictionary. With growing technological advancement, electronic dictionary keeps on emerging. Current existing electronic dictionaries are limited with functionality to translate for multiword correctly. This paper aims to discover a searching algorithm that can read single and two words (multiword) in a Malay or English language and translate it correctly to another language, either Malay or English. The objectives of the study is to develop a Mobile Dictionary system, namely MobileDic which able to cater for single and multiword translation in Malay and English language in J2ME-enabled mobile phones. The system incorporates a searching algorithm, by using Hashtable function. The system prototype should be able to recognize whether the input word is a single or multiword and intelligently translate the word matched by Hashtable key and value. The multiword will have its own separate database or corpus listing all the possible second word after the first word of that multiword. The output of this system will be evaluated by users who already have experienced in using existing electronic dictionaries based on MobileDic accuracy as well as its usefulness. As a conclusion, MobileDic is able to improve current situation and can be a useful look-up source especially to students and tourist.